THE EFFECT OF DISTANCE BETWEEN RESIDENCE AND CAMPUS ON STUDENTS LEARNING MOTIVATION IN GEOGRAPHY EDUCATION AT TANJUNGPURA UNIVERSITY - Kurnia, Kurnia; Anasi, Putri Tipa; Harjanti, Diah Trismi (GEOREFERENCE, 2024)
The research investigates the relationship between the distance geography education students live from campus and their motivation to study. It uses a quantitative descriptive survey method, with data collected through documentation, indirect communication, and observation. The study defines short distances as travel times of 15 minutes or less, either by walking (within 1 km) or by vehicle (within 2 km), while longer travel times exceed 15 minutes. A sample of 92 respondents was selected using the Harry King Nomogram formula. The data was analyzed through normality and linearity tests, simple linear regression analysis, and hypothesis testing. Results show that students' residence distance and mode of transportation affect the time taken to travel to campus. The strongest motivational factor is the desire to succeed, rated at 84%. Hypothesis testing revealed that distance significantly influences study motivation, with an R Square value of 0.168, indicating a 16.8% contribution. Thus, the study concludes that the distance from home to campus significantly impacts students' learning motivation.